How do Islamic corporate social responsibility and environmental performance relate to company value? - Rahmayanti, Dini; Arifah, Ziinatul; Jamilah, Putri (Faculty of Economics, Universitas Islam Indonesia, 2025)
Purpose – This study aims to provide a comprehensive analysis of the impact of the investment opportunity set (IOS), profitability, Islamic corporate social responsibility (ICSR), and environmental performance (EP) on the value of environmentally sensitive companies. The research explores both short-term and long-term impacts of these variables on corporate value. Methodology – This study utilized Vector Error Correction Model (VECM) approach to analyze annual data from 2016 to 2022, focusing on environmentally sensitive companies in the Indonesian Sharia stock index. Findings – The VECM method yielded several key findings, including no significant impact of IOS on company value in either short or long term. However, variables such as ICSR, environmental performance, and profitability exhibited a significant influence on company value over the same timeframe.Implications – This study suggests that, to enhance credibility, companies should prioritize financial stability, credibility in financial reporting, social responsibility, and environmental regulations. They should identify the best investment opportunities and collaborate with the government to achieve environmental sustainability.Originality – Our study seeks to delve into the relationship between several variables, including IOS, profitability, ICSR, environmental performance, and the overall value of environmentally sensitive companies. This topic has not been explored in-depth by previous research, and our study aims to shed light on both short- and long-term effects of these factors on corporate value.